The Borg Scale at high altitude - Küpper, Thomas; Heussen, N.; Morrison, Audry; Schöffl, Volker; Basnyat, Buddha; Hillebrandt, David; Milledge, Jim; Steffgen, Jürgen; Meier, Beate (Health Promotion & Physical Activity, 2021)
Introduction: The Borg Scale for perceived exertion is well established in science and sport to keep an appropriate level of workload or to rate physical strain. Although it is also often used at moderate and high altitude, it was never validated for hypoxic conditions. Since pulse rate and minute breathing volume at rest are increased at altitude it may be expected that the rating of the same workload is higher at altitude compared to sea level. Material and methods: 16 mountaineers were included in a prospective randomized design trial. Standardized workload (ergometry) and rating of the perceived exertion (RPE) were performed at sea level, at 3,000 m, and at 4,560 m. For validation of the scale Maloney-Rastogi-test and Bland-Altmann-Plots were used to compare the Borg ratings at each intensity level at the three altitudes; p < 0.05 was defined as significant. Results: In Bland-Altmann-Plots more than 95% of all Borg ratings were within the interval of 1.96 x standard deviation. There was no significant deviation of the ratings at moderate or high altitude. The correlation between RPE and workload or oxygen uptake was weak. Conclusion: The Borg Scale for perceived exertion gives valid results at moderate and high altitude – at least up to about 5,000 m. Therefore it may be used at altitude without any modification. The weak correlation of RPE and workload or oxygen uptake indicates that there should be other factors indicating strain to the body. What is really measured by Borg’s Scale should be investigated by a specific study.